Experimental study on multibody systems with clearance joints - Lankarani, H. M. (2004)
A comprehensive experimental study on the dynamic responses of slider-crank mechanism with clearance joints is presented in this work. The main sub-assembly of the experimental test rig consisted of slider-crank mechanism with an adjustable radial clearance at the revolute joint that connected the slider and the connecting rod. The motion of the slider was measured with a linear transducer and an accelerometer. Dynamic tests at different operating crank speeds and with several clearance sizes were performed. The slider acceleration (impact acceleration) was used as a measure of the impact severity. The results obtained clearly demonstrated the severe dynamical behavior in a clearance joint and they provide a qualitative measure of the associated fatigue and wear phenomena in which the components must be reliably operate in real joints.